Biologics modulate antinuclear antibodies, immunoglobulin E, and eosinophil counts in psoriasis patients. Issue 11 (8th August 2021) - Sugiura, Riichiro; Terui, Hitoshi; Shimada‐Omori, Ryoko; Yamazaki, Emi; Tsuchiyama, Kenichiro; Takahashi, Toshiya; Aiba, Setsuya; Yamasaki, Kenshi
Abstract: Psoriasis is a chronic disease centered on tumor necrosis factor (TNF), interleukin (IL)‐23, and IL‐17 axis. While psoriasis patients benefit from biologics targeting TNF, IL‐17s, and IL‐23 nowadays, suppression of these molecules could modulate the balances of immune systems. However, the incidence of autoimmune disease and T‐helper 2 reaction during biologic treatments for psoriasis patients is not well documented. We retrospectively examined antinuclear antibody (ANA), eosinophil counts, and immunoglobulin E (IgE) levels for psoriasis patients who underwent biologic treatments in our dermatology clinic from June 10, 2010 to January 29, 2020. A cumulative total of 199 biologic treatments were performed for a total of 128 psoriasis patients. Compared to the non‐biologic group of 109 psoriasis patients who received non‐biologic treatment, patients treated with infliximab showed more incidents of high ANA (14%, p  = 0.039) and high eosinophils (14%, p  = 0.021). The use of brodalumab increased incidents of high eosinophils (21%, p  = 0.005) but did not affect increase in ANA and IgE. The increase in high IgE level was observed significantly more during the use of risankizumab (15%, p  = 0.011). Methotrexate was the most frequently used concomitant systemic treatment, but methotrexate did not affect ANA, eosinophil counts, and IgE levels. Since the biologics for psoriasis treatment modulate the balance of T‐helper cells, careful observation is required to detect unexpected changes of systemic immune conditions under biologic treatments.